OP0167 SUCCESSFUL WITHDRAWAL OF MYCOPHENOLATE MOFETIL IN QUIESCENT SLE: RESULTS FROM A RANDOMIZED TRIAL. (2nd June 2020) - Chakravarty, E.; Utset, T.; Kamen, D. L.; Contreras, G.; Mccune, W. J.; Kalunian, K. C.; Aranow, C.; Clowse, M.; Goldmuntz, E.; Springer, J.; Keyes-Elstein, L.; Barry, B.; et al.
Abstract : Background: Trials and clinical observations have demonstrated the efficacy of mycophenolate mofetil (MMF) for SLE treatment. Long-term use of MMF is associated with adverse events, pregnancy risks, drug monitoring, and increased cost. Current management continues therapy indefinitely. Whether immunosuppression may be safely withdrawn or whether risks of withdrawal outweigh the benefits of continuation is unknown. Objectives: To compare rates of clinically significant disease reactivation (CSDR), major flares, and all flares in patients with quiescent SLE on stable MMF randomized to maintain or withdraw MMF. The goal is to provide guidance for clinicians and patients on the risks of MMF withdrawal. Methods: Adults with quiescent SLE (SELENA-SLEDAI without serologies <4) receiving MMF for ≥2 years for nephritis or ≥ 1 year for non-nephritis were randomized 1:1 to unblinded MMF (maintenance arm, MA) or to a 12-week taper off MMF (withdrawal arm, WA) and followed through 60 weeks. Subjects were on stable hydroxychloroquine; steroids limited to ≤ 10 mg. CSDR, defined as a SLEDAI flare requiring immunosuppression, BILAG flares and adverse events were assessed. Event rates and time to flare were compared using Kaplan-Meier. Results: 102 subjects were randomized (50 MA, 52 WA); 1 subject in each arm was ineligible and 10 terminated early (7 MA, 3 WA). Mean disease duration was 13 years; 76% had a history of nephritis; mean baseline SLEDAI was 2.2. 5 MA subjects (10%) had CSDR, compared to 9 WA (17%). Median time to CDSR was 38 weeks in both arms. BILAG A flares occurred in 1MA subject (pancreatitis) vs. 4 WA (cranial neuropathy, panniculitis, 2 nephritis). Kaplan-Meier curves overlapped for CDSR, BILAG A flares, and all SLEDAI flares (Figure). Based on these data, we are 86% confident that the increased risk of CDSR with MMF withdrawal is less than 15% over 60 weeks. AEs were similar between groups; infections occurred more commonly in MA (63 vs. 49). Conclusion: In this cohort of subjects with quiescent SLE on long term MMF serious flares occurred infrequently in subjects continuing or withdrawing MMF without differences in time to flare. MMF withdrawal may be considered in subjects with prolonged quiescent disease. Disclosure of Interests: Eliza Chakravarty: None declared, Tammy Utset: None declared, Diane L Kamen Consultant of: Consulted on SLE survey development for Lilly and consulted on SLE trial protocol development for EMD Serono in 2019, Gabriel Contreras Grant/research support from: Genentech, Merck, Consultant of: Genentech, Merck, William Joseph McCune: None declared, Kenneth C Kalunian: None declared, Cynthia Aranow: None declared, Megan Clowse Grant/research support from: GSK, Pfizer, Consultant of: UCB, Astra-Zeneca, Speakers bureau: UCB, Ellen Goldmuntz: None declared, Jessica Springer: None declared, Lynette Keyes-Elstein: None declared, Bill Barry: None declared, Ashley Pinckney: None declared, Judith James: None declared